Potensi Sumberdaya Arkeologi Maritim di Pesisir Pantai Tejakula, Buleleng, Bali - Wayan Sumerata; Gendro Keling; Ati Rati Hidayah (Berkala Arkeologi Sangkhakala, 2017)
AbstractTejakula has long been attracted a number of researchers as a potential site to be developed. The site is located along the coast of North Bali which, according to several sources, was part of a sailing route for ships to and from other areas in the Indonesian Archipelago and even foreign places. Among the research locations are Pantai Bangsal (Bangsal Coast) Site at the hamlet of Geretek Beberapa (Dusun Geretek) and along Bondalem Beach. The method of data collections were bibliographical study, land survey, and underwater exploration using SCUBA Diving technique. Results of this research include information about the contour and condition of the ocean floor of Sambirenteng, which are trough and muddy, as well as the finding of traces of a rock structure and pottery on Bangsal Coast, Geretek Hamlet, Sambirenteng Village. The structure and pottery show that there were activities on the coast area that were related to harbor or habitation. Furthermore, there are also prehistoric pottery finds, which are now submerged under the water because of severe beach abrasion at the village of Bondalem.AbstrakSitus Tejakula sejak dulu sudahdilirik oleh peneliti sebagai situs yang potensial untuk dikembangkan. Situs ini berada di kawasan pesisir Pantai Bali Utara yang menurut beberapa sumber merupakan jalur pelayaran bagi kapal dari berbagai wilayah lain di Nusantara bahkan dari luar negeri. Beberapa titik lokasi penelitian ini antara lain adalah Situs Pantai Bangsal di Dusun Geretek, dan Sepanjang Pantai Bondalem. Metode Pengumpulan data dilakukan dengan studi pustaka, survei berupa observasi di darat dan juga di bawah air dengan menggunakan teknik SCUBA Diving. Hasilnya diperoleh kontur dan kondisi dasar laut Sambirenteng yang berupa palung dan berlumpur, serta temuan bekas struktur berupa batu padas di Pantai Bangsal, Dusun Geretek, Desa Sambirenteng. Temuan struktur dan gerabah ini memperkuat adanya aktifitas di sekitar pantai yang terkait dengan aktivitas pelabuhan atau permukiman. Selain itu temuan gerabah dari masa prasejarah yang kondisi saat ini di bawah permukaan air karena abrasi pantai yang parah di Desa Bondalem.